1993
DOI: 10.1007/bf02783175
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selenium deficiency on Ca transport function of sarcoplasmic reticulum and lipid peroxidation in rat myocardium

Abstract: Two groups of weanling Sprague-Dawley rats were fed a low-selenium basal diet (Se 0.009 mg/kg) and the same diet supplemented with sodium selenite (Se 0.25 mg/kg), respectively, for 1, 2, and 3 months. At each feeding time, the Ca(2+)-ATPase activity, Ca2+ uptake rate and the capacity of Ca2+ uptake in isolated cardiac sacroplasmic reticulum from the Se-deficient rats were decreased significantly compared to those from the Se-supplemented rats, the contents of lipid peroxide in postmitochondrial supernatant an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…between Se and vitamin E is well known, and the metabolism of one of these is influenced by the other (Fisher &manger, 1977). It has been demonstrated that the oxidative damage in many tissues is more severe during double Se and vitamin E deficiency than with deficiency of either antioxidant alone (Arthur et al 1988;You-Zhen et al 1993;Lee & Csallany, 1994;Kuo et al 1995). Additionally, Se and vitamin E may have important roles in biological processes of importance for the cardiovascular system that do not necessarily relate to their antioxidant function (Arthur et al 1993;Dutta-Roy et al 1994).…”
mentioning
confidence: 99%
“…between Se and vitamin E is well known, and the metabolism of one of these is influenced by the other (Fisher &manger, 1977). It has been demonstrated that the oxidative damage in many tissues is more severe during double Se and vitamin E deficiency than with deficiency of either antioxidant alone (Arthur et al 1988;You-Zhen et al 1993;Lee & Csallany, 1994;Kuo et al 1995). Additionally, Se and vitamin E may have important roles in biological processes of importance for the cardiovascular system that do not necessarily relate to their antioxidant function (Arthur et al 1993;Dutta-Roy et al 1994).…”
mentioning
confidence: 99%